Impacto da estimulação transcraniana por corrente contínua na atividade elétrica cerebral de pacientes com zumbido crônico: ensaio clínico, duplo- cego, placebo-controlado - Souza, Dayse da Silva (2017)
Tinnitus is a symptom characterized by the perception of a sound in the absence of an external stimulus. It results from alterations in the auditory neural network, caused by abnormal excitability and increased neuronal synchronicity in the auditory centers. Due to the central component of the symptom, neuromodulatory techniques have gained prominence, among them Transcranial Direct Current Stimulation - tDCS. The focus of the present study was to identify not only whether tDCS was effective in the treatment of tinnitus, but also whether it could modulate the cortical electrical activity of patients with the symptom. Three articles were developed: the first one a case study, the second one a protocol article and the third one an empirical study of the results of the first clinical trials. The case study was based on a 23-year-old female patient with bilateral tinnitus and revealed that tDCS could modulate the intensity, frequency and auditory discomfort caused by the symptom, measured with Acufenometry, and Visual Analogue Scale - VAS. Based on this assumption, it was decided to combine behavioral measures with an electrophysiological marker of the therapeutic benefit of tDCS; this way the second article corresponded to a protocol article, whose objective was to expose the procedures that were adopted in the double-blind, placebo-controlled clinical trial study that allied tDCS application to the electroencephalography exam. The third article revealed the results of the first clinical trial that was performed using 22 patients with tinnitus and 11 healthy individuals, which showed that tDCS could modulate the presentation of the frequency bands Alpha, Beta and Theta in the experimental groups corresponding with placebo and control, mainly in frontal, temporoparietal and limbic regions to reduce the auditory discomfort caused by the symptom. It was concluded that tDCS was promising in the treatment of tinnitus with observed improvement in behavioral and electrophysiological data.